2022
DOI: 10.1155/2022/9111681
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-579 Inhibits Lung Adenocarcinoma Cell Proliferation and Metastasis via Binding to CRABP2

Abstract: Background. Lung cancer is the cancer with the highest morbidity and mortality. Lung adenocarcinoma (LUAD) is a subtype of lung cancer. The aim of this study is to explore the functions of miR-579 and CRABP2 in lung adenocarcinoma. Methods. Cell counting kit-8 (CCK-8) and colony formation assays were applied to calculate cell proliferative abilities. Transwell assay was utilized to measure cell invasive ability. Results. MiR-579 is low expressed in LUAD tissues and cell lines. MiR-579 inhibits cell viability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Indeed, besides the effects on BRAF oncogenic signaling, miR-579-3p is also able to target MDM2 oncoprotein [ 13 ] which is fundamental to sustain anti-apoptotic signals responsible for drug tolerant/resistant states [ 40 ]. In line with our findings, miR-579-3p oncosuppressive role has been also described in other solid tumors, like lung and hepatocellular adenocarcinomas [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, besides the effects on BRAF oncogenic signaling, miR-579-3p is also able to target MDM2 oncoprotein [ 13 ] which is fundamental to sustain anti-apoptotic signals responsible for drug tolerant/resistant states [ 40 ]. In line with our findings, miR-579-3p oncosuppressive role has been also described in other solid tumors, like lung and hepatocellular adenocarcinomas [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, CRABP2 can interact with HuR, enhancing the binding ability of HuR to target RNA and increasing RNA stability [ 13 ]. Currently, abnormal expression of CRABP2 has been found in various tumors [ 14 17 ], either upregulated or downregulated, and its role in tumors is not yet clear. The expression of CRABP2 in breast cancer tissues is significantly up-regulated, and it may become a new diagnostic marker for breast cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the Wnt/β-catenin pathway contribute to the development/progression of several types of cancer, including NSCLC (17). Numerous studies have demonstrated the dysregulation of miRNAs in several types of cancer (18)(19)(20), and that aberrantly expressed miRNAs are related to dysregulation of the Wnt/β-catenin signaling (6). Numerous miRNAs inactivate the Wnt/β-catenin signaling pathway to affect the progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%